A Review of Soil Nailing Design Approaches - Taib, S.N.L. (Universiti Malaysia Sarawak (UNIMAS), 2010)
A number of design manuals and recommendations; namely by the HA 68 [4] (U.K.), BS8006 [1]. RDGC [7] (France) and FHWA [5] (USA) are available for soil nailing. This paper will focus on the different approaches, specifically on the assumptions made for the design of soil nailing structures.